1990
DOI: 10.1111/j.1476-5381.1990.tb15831.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of central injection of acetylcholine in anaesthetized dogs: a role for vasopressin release

Abstract: 1 The effect of an intracisternal injection of 20Ougkg-' of acetylcholine was studied on systolic and diastolic blood pressures, heart rate, and plasma levels of noradrenaline, adrenaline, vasopressin, plasma renin activity and atrial natriuretic factor in chloralose-anaesthetized dogs, 8 of which were normal and 7 with diabetes insipidus (deprived of vasopressin secretion by surgical lesion of the hypothalamoneurohypophysial system). 2 Acetylcholine significantly increased systolic and diastolic blood pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
2

Year Published

1994
1994
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
4
8
2
Order By: Relevance
“…In fact, most of the available studies published on this topic have been performed in anaesthetized animals (for review, see Brezenoff & Giuliano, 1982). In anaesthetized animals, it is generally reported that ACh induces a rise in blood pressure mediated by an increase in both sympathetic tone and the release of AVP (Krstic & Djurcovic, 1978;Buccafusco & Brezenoff, 1979;Rascol et al, 1990). The central effects of cholinomimetic drugs on heart rate and Ad release are on the contrary extremely variable according to the literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, most of the available studies published on this topic have been performed in anaesthetized animals (for review, see Brezenoff & Giuliano, 1982). In anaesthetized animals, it is generally reported that ACh induces a rise in blood pressure mediated by an increase in both sympathetic tone and the release of AVP (Krstic & Djurcovic, 1978;Buccafusco & Brezenoff, 1979;Rascol et al, 1990). The central effects of cholinomimetic drugs on heart rate and Ad release are on the contrary extremely variable according to the literature.…”
Section: Discussionmentioning
confidence: 99%
“…injection of a single dose of 20 Mg kg-'; acetylcholine chloride (Lemotte and Boinot labs) dissolved into a 0.9% w/v NaCl solution in the ACh protocol. This dose was known to induce a mean rise in blood pressure of 30 mmHg in anaesthetized dogs according to previous comparable experiments performed in our laboratory (Rascol et al, 1990). The effects of i.c.…”
Section: General Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Centrally administered ACh or cholinergic agents increase arterial BP [53] because of the increase in sympathetic nerve tone and the acceleration of vasopressin release [53][54][55]. Systemic injection of ChE inhibitor increases systolic and diastolic BP [27,56].…”
Section: Effect Of Inhibition Of Cholinesterase On Arterial Blood Prementioning
confidence: 99%